Electrochemical aptasensor for 2-amino-2-thiazoline-4- 2 carboxylic acid (ATCA), a metabolite for cyanide 3 poisoning - Yusof, Nor Azah; Mohamad Anas Khan, Hairunnisa; Yee, Yu Choo; Alang Ahmad, Shahrul Ainliah; Raston, Nurul Hanunahmad; Abd Rahman, Siti Fatimah (Nature Publishing Group, 2024)
An alternative biomarker for assessing the cyanide levels in postmortem materials is crucial for investigating acute cyanide intoxication. Herein, an aptamer–ligand biorecognition system with high specificity was developed to detect acute cyanide poisoning via its secondary metabolite, 2-amino-2-thiazoline-4-carboxylic acid (ATCA). Potential aptamers were screened from a random library of 66-base single-stranded DNA using GO-SELEX, with individual aptamers being identified through single-stranded DNA sequencing. Molecular docking was employed to predict the affinity of these aptamers toward ATCA and selected counter-targets; these predictions were confirmed using thermodynamic analysis with an isothermal titration calorimeter. Owing to its label-free biomolecular binding interactions, Apt46 exhibited the highest affinity against ATCA and notable selectivity against structurally similar counter-targets. Thus, an amino-tagged Apt46 binding aptamer was attached to a carbon electrode modified with EDC–NHS-activated graphene oxide. The binding of Apt46 to ATCA was quantified by measuring current changes using differential pulse voltammetry. The aptasensor achieved a detection limit of 0.05 µg/mL and demonstrated suitability for detecting ATCA across various biological matrices, with the high recovery percentages ranging from 92.29 to 114.22%. Overall, the proposed ATCA aptasensor is promising for identifying ATCA metabolites in cases of acute cyanide expose.